Increased Water-Soluble Yellow Monascus Pigment Productivity via Dual Mutagenesis and Submerged Repeated-Batch Fermentation of Monascus purpureus - Bai, Jie; Gong, Zihan; Shu, Meng; Zhao, Hui; Ye, Fanyu; Tang, Chenglun; Zhang, Song; Zhou, Bo; Lu, Dong; Zhou, Xiang; Lin, Qinlu; Liu, Jun (Frontiers in Microbiology, 2022)
Monascus pigments (MPs) have been used in the food industry for more than 2,000 years and are known for their safety, bold coloring, and physiological activity. MPs are mainly yellow (YMPs), orange (OMPs), and red (RMPs). In this study, a mutant strain Monascus purpureus H14 with high production of water-soluble YMPs (WSYMPs, λmax at 370 nm) was generated instead of primary YMPs (λmax at 420 nm), OMPs (λmax at 470 nm), and RMPs (λmax at 510 nm) produced by the parent strain M. purpureus LQ-6 through dual mutagenesis of atmospheric and room-temperature plasma and heavy ion beam irradiation (HIBI), producing 22.68 U/ml extracellular YMPs and 10.67 U/ml intracellular YMPs. WSYMP production was increased by 289.51% in optimal conditions after response surface methodology was applied in submerged fermentation. Application of combined immobilized fermentation and extractive fermentation improved productivity to 16.89 U/ml/day, 6.70 times greater than with conservative submerged fermentation. The produced WSYMPs exhibited good tone stability to environmental factors, but their pigment values were unstable to pH, light, and high concentrations of Ca2+, Zn2+, Fe2+, Cu2+, and Mg2+. Furtherly, the produced exYMPs were identified as two yellow monascus pigment components (monascusone B and C21H27NO7S) by UHPLC-ESI-MS. This strategy may be extended to industrial production of premium WSYMPs using Monascus.